Assessment of Groundwater Quality and Health Risks in Bardsir Plain (Iran) Using WQI, TOPSIS, and CDI-HQ - Marjan Salari; Mohammad Ali Mohammad Jafar Sharbaf; Hadiseh Hosseini; Hanie Abbaslou (Scientific Reports, 2026)
Abstract This study presents a novel, integrated framework for the holistic assessment of groundwater security in semi-arid regions, utilizing a nine-year, high-resolution dataset from Iran’s Bardsir Plain. The novelty stems from its comprehensive integration of hydrochemical analysis, multi-index evaluation, decision-support modeling, and quantitative health risk assessment. Hydrochemical analysis, employing Gibbs diagrams and Chloro-Alkaline indices, indicates that groundwater composition is primarily controlled by natural processes such as rock weathering, evaporation, and reverse cation exchange. Water Quality Index (WQI) values suggest generally favorable water quality, with most of wells rated ‘Good’ to ‘Excellent’ (scores ranging from 21.143 at Well 40W [Excellent] to 106.014 at Well 17W [Poor]). Significantly, integrating multiple Water Quality Indices with a Multi-Criteria Decision-Making (MCDM) model resolved classification inconsistencies. The TOPSIS method effectively reconciled divergent drinking and irrigation index rankings, yielding unified suitability scores from 0.998 (Well 30W) to 0.215 (Well 17W). Finally, health risks were quantified using the Hazard Quotient (HQ). Regarding non‑carcinogenic health risks, most major ions exhibited negligible hazards. However, chloride presented a mean HQ of 4.03, indicating a low level potential concern, particularly for children. Beyond our case study, this integrated framework offers a practical and replicable model for managing groundwater in other semi-arid regions. It clearly highlights the need for continuous water quality surveillance and the timely implementation of recharge systems in the most vulnerable areas two strategic measures that are critical for ensuring long-term water security.